(untitled) (Baghdad Science Journal, 2024)
In latest decades, genetic methods have developed into a potent tool in a number of life-attaching applications. In research looking at demographic genetic diversity, QTL detection, marker-assisted selection, and food traceability, DNA-based technologies like PCR are being employed more and more. These approaches call for extraction procedures that provide efficient nucleic acid extraction and the elimination of PCR inhibitors. The first and most important stage in molecular biology is the extraction of DNA from cells. For a molecular scientist, the high quality and integrity of the isolated DNA as well as the extraction method’s ease of use and affordability are crucial factors. The present study was designed to establish a simple, fast and inexpensive method for DNA extraction from human peripheral blood (normal male n=2, age 24 years old, patient male (prostate cancer) n=2, age 65 years old) by comparing between them, and aimed to standardize a protocol of DNA extraction using five extraction protocols. The first method was the modified organic method by using sodium perchlorate instead of organic solvent (phenol, chloroform), sodium perchlorate advantage comes from its cheap price and low storage and shipping requirements, the second was the enzymatic method by using proteinase K, third method was done by using detergent, the fourth used phenol-chloroform; finally fifth one was salting out method. The result showed that the organic method gives a good DNA yield and needs relatively short time while the enzymatic method gives an excellent DNA purity which are more suitable for PCR by comparing five protocols using the spectrophotometer and Nanodrop technetium in addition to electrophoresis. Through the use of the five suggested procedures, the PCR multiplication of the P53 gene with the isolated DNA was effectively carried out. This indicates that, with the exception of the detergent approach, there were no significant inhibiting substances for Taq polymerase in the final solution.